2011
DOI: 10.1172/jci45887
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue remodeling and obesity

Abstract: To fulfill its role as the major energy-storing tissue, adipose has several unique properties that cannot be seen in any other organ, including an almost unlimited capacity to expand in a non-transformed state. As such, the tissue requires potent mechanisms to remodel, acutely and chronically. Adipocytes can rapidly reach the diffusional limit of oxygen during growth; hypoxia is therefore an early determinant that limits healthy expansion. Proper expansion requires a highly coordinated response among many diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
1,420
3
47

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,585 publications
(1,497 citation statements)
references
References 103 publications
27
1,420
3
47
Order By: Relevance
“…In this regard, Khan et al reported that mice lacking collagen VI, which is expressed abundantly in adipose tissue, exhibit the uninhibited adipose tissue expansion and substantial improvements in insulin sensitivity on a high-fat diet [67]. These findings suggest that reduced lipid storage in obese adipose tissue may contribute to ectopic lipid accumulation in non-adipose tissues such as the liver, skeletal muscle, and pancreas, where lipotoxicity impairs their metabolic functions [10,[71][72][73]. Although the molecular mechanisms underlying adipose tissue fibrosis are still largely unknown, recent evidence suggests that a PPARγ-fibroblast growth factor 1 (FGF1) axis is required for obesity-induced adipose tissue remodeling [74].…”
Section: Novel Regulators Of Adipose Tissue Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, Khan et al reported that mice lacking collagen VI, which is expressed abundantly in adipose tissue, exhibit the uninhibited adipose tissue expansion and substantial improvements in insulin sensitivity on a high-fat diet [67]. These findings suggest that reduced lipid storage in obese adipose tissue may contribute to ectopic lipid accumulation in non-adipose tissues such as the liver, skeletal muscle, and pancreas, where lipotoxicity impairs their metabolic functions [10,[71][72][73]. Although the molecular mechanisms underlying adipose tissue fibrosis are still largely unknown, recent evidence suggests that a PPARγ-fibroblast growth factor 1 (FGF1) axis is required for obesity-induced adipose tissue remodeling [74].…”
Section: Novel Regulators Of Adipose Tissue Inflammationmentioning
confidence: 99%
“…In other words, stromal cells change dramatically in number and cell type during the course of obesity. Such dynamic histological changes observed in obese adipose tissue can be referred to as "adipose tissue remodeling" [10,17,18]. In this regard, recent evidence suggests that the interaction between mature adipocytes and stromal cells in adipose tissue plays a critical role in the regulation of adipocytokine production [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several chronic diseases, such as obesity,20 metabolic syndrome and lipodystrophy,21 induce AT remodelling, involving two major processes: adipose cell morphometric changes (hypertrophy or atrophy) and immune cells accumulation. Inflammation, endoplasmatic reticulum stress and hypoxia are also part of the general biologic alterations subsidizing the attraction and retention of inflammatory cells in AT 22.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, excess of nutrients causes an increase in the size (hypertrophy) and number (hyperplasia) of adipocytes during the development of obesity (Sun et al 2011). However, the ability of AT to store excess energy as triglycerides is limited, as determined by both genetic and environmental factors.…”
Section: Introductionmentioning
confidence: 99%